Treatment of ruptured middle cerebral artery aneurysms by endovascular approach: a single-center experience. (4th May 2017) - Zhao, Xintong; Li, Zhenbao; Fang, Xinggen; Liu, Jiaqiang; Wu, Degang; Lai, Niansheng
Abstract : Purpose : The optimal treatment modalities of ruptured middle cerebral artery aneurysm are still controversial. The objective of this study is to analyze the outcomes of patients with ruptured middle cerebral artery aneurysms treated by endovascular coiling. Materials and methods : From October 2011 to October 2015, 67 patients with 71 ruptured middle cerebral artery aneurysms received endovascular coiling in our hospital. We retrospectively reviewed the clinical, radiologic records and outcomes. Results : Of all the 71 aneurysms (67 patients), 42 were treated by coil embolization merely, 27 by stent-assisted coiling and 2 unruptured aneurysms in patients with bilateral middle cerebral artery aneurysms without receiving treatment. Complete occlusion was achieved in 82.6% (57/69) of all the procedures. Each of incomplete and partial occlusion rates was 8.7% (6/69). Intraoperative rupture of aneurysms occurred in two procedures (2.9%). Thrombogenesis occurred in eight procedures (11.6%). Brain infarction occurred in eight patients (11.9%). Post-operative rebleeding occurred in seven patients (10.4%). Sixty-three patients were followed at a mean follow-up of 8.24 ± 7.16 months. The mortality and good outcome rate were 3.2% and 90.5%, respectively. Aneurysm recurrence occurred in 6 (13.3%) of the 45 aneurysms at a mean follow-up of 8.44 ± 7.83 months. Conclusions : Endovascular coiling is effective for patients with ruptured middle cerebral artery aneurysms. Individualized treatment should be assessed by experienced specialist. It is essential to perform randomized large trials to confirm the efficiency of endovascular coiling.